1984
DOI: 10.1063/1.447034
|View full text |Cite
|
Sign up to set email alerts
|

Solute–solute interactions in water. II. An analysis through the Kirkwood–Buff integrals for 14 organic solutes

Abstract: From accurate data of activities (a), partial molar volumes (V̄), and compressibility (K) of binary aqueous mixtures, the so-called Kirkwood–Buff integrals Gij defined by Gij=∫∞0 [ gij(r) −1] 4πr2 dr=f(a,V̄,K), (i=1,2; j=1,2), have been calculated in the whole concentration range. Fourteen water(1)-organic cosolvent(2) systems [methanol, ethanol, 1-propanol, 1-butanol, 2-methyl-2-propanol, acetonitrile, acetone, dimethylsulfoxide, tetrahydrofuran, piperidine, pyridine, 1,4-dioxane, 2-aminoethanol, 2-(dimethyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
251
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(268 citation statements)
references
References 52 publications
15
251
1
Order By: Relevance
“…Below we present selected literature data showing how unclear it is. On the basis of comparative studies of many aqueous systems Matteoli and Lepori stated that the hydrophilic group of acetonitrile reduces its hydrophobicity almost as strong as the OH or NH 2 groups do [1]. Let us note that the series of hydrophilic character of different groups proposed by Matteoli and Lepori is in contradiction with findings of Wakisaka et al [2], while according to the former authors methanol and acetonitrile should be similar in hydrophobic character (methanol should be even weaker).…”
Section: Introductioncontrasting
confidence: 53%
“…Below we present selected literature data showing how unclear it is. On the basis of comparative studies of many aqueous systems Matteoli and Lepori stated that the hydrophilic group of acetonitrile reduces its hydrophobicity almost as strong as the OH or NH 2 groups do [1]. Let us note that the series of hydrophilic character of different groups proposed by Matteoli and Lepori is in contradiction with findings of Wakisaka et al [2], while according to the former authors methanol and acetonitrile should be similar in hydrophobic character (methanol should be even weaker).…”
Section: Introductioncontrasting
confidence: 53%
“…The middle panel shows the RKBI calculated from the various correlation functions shown in the left panel. It is obvious that, if the initial form should have been retained, it would lead to value of the KBI or the order of 2500, which correspond to the peak of the RBKI (as often used in various publications), and too large compared to the various experimental estimates from (Matteoli E. & Lepori L., 1984) shown in brown horizontal line and our own experimental value (Perera et al, 2006) shown in cyan line. The TS extension (blue curve) allows to bring the wrong initial tendency to the value very close to our experimental estimate.…”
Section: Aqueous-tbutanol Mixtures: An Illustration Of the Molecular mentioning
confidence: 98%
“…In a landmark paper (Matteoli E. & Lepori L., 1984), Matteoli and Lepori have provided the behaviour of the experimental KBI for a variety of binary mixtures. The reproduction of this data by computer simulations and its interpretation is still a challenging open problem.…”
Section: Kirkwood-buff Integrals and Computer Simulationsmentioning
confidence: 99%
“…7, we report the KBI for both mixture models (symbols), together with the expected ideal KBI (lines). These ideal KBI are defined from the relations derived from the KB theory, 14,15,24 …”
Section: Kirkwood-buff Integralsmentioning
confidence: 99%
“…In contrast, most aqueous mixtures are strongly nonideal. 15,24 However, some aqueous mixtures, such as aqueousdimethylsulfoxyde (DMSO) mixtures are surprisingly ideal from the KBI point of view. 25 Our interpretation of this ideality is through our finding that, in such mixtures, water forms linear clusters, and the interactions between such clusters and DMSO are near ideal.…”
Section: Introductionmentioning
confidence: 99%